Preliminary Compositional Evidence of Provenance of Ceramics from Hatahara Archaeological Site, Central Amazonia - K. P. Nunes; R. G. Toyota; P. M. S. Oliveira; E. G. Neves; E. A. A. Soares; C. S. Munita (Journal of Chemistry)
One hundred twenty four ceramic fragments and six clay samples from the Hatahara archaeological site in Amazonas state, Brazil, were analyzed using instrumental neutron activation analysis, INAA, to determine the concentration of twenty chemical elements: Ce, Co, Cr, Cs, Eu, Fe, Hf, K, La, Lu, Na, Nd, Rb, Sc, Ta, Tb, Th, U, Yb, and Zn. The dataset was submitted to multivariate statistical analysis. The classification was done by cluster analysis and discriminant analysis. The results demonstrated the occurrence of four different groups of ceramics, which represent three archaeological phases: Paredão, Manacapuru, and Guarita. This data is consistent with previous traditional petrographic examination of the ceramic samples. Based on probability measures, the great majority of the ceramics are considered to be local in origin.